2018
DOI: 10.1016/j.ibusrev.2017.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Why do self-initiated expatriates quit their jobs: The role of job embeddedness and shocks in explaining turnover intentions

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 79 publications
5
67
0
7
Order By: Relevance
“…By definition, 'self-initiated' expatriates (SIEs) are assumed to show personal initiative when relocating abroad (e.g., Andresen, Bergdolt, Dickmann, & Margenfeld, 2014;Cerdin & Selmer, 2014;Tharenou, 2015). Self-initiated international mobility is described as a choice (Doherty, Dickmann, & Mills, 2011;Hussain & Deery, 2018) made by individuals who decide on their own to go abroad (Dorsch, Suutari, & Brewster, 2013). Without organizational assistance (Begley, Collings, & Scullion, 2008), they selfarrange new employment overseas (Cerdin & Selmer, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…By definition, 'self-initiated' expatriates (SIEs) are assumed to show personal initiative when relocating abroad (e.g., Andresen, Bergdolt, Dickmann, & Margenfeld, 2014;Cerdin & Selmer, 2014;Tharenou, 2015). Self-initiated international mobility is described as a choice (Doherty, Dickmann, & Mills, 2011;Hussain & Deery, 2018) made by individuals who decide on their own to go abroad (Dorsch, Suutari, & Brewster, 2013). Without organizational assistance (Begley, Collings, & Scullion, 2008), they selfarrange new employment overseas (Cerdin & Selmer, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…What emerged about self-expatriation raises the issue of SIEs' country and ethnic origin in the experience and outcomes of that endeavor. In recent years, and as work on self-initiated expatriation grows in volume, authors have looked at various factors to explain SIEs' adaptation and success in host countries (e.g., Bozionelos, 2009;Cao et al, 2013;Selmer et al, 2015;Husssain and Deery, 2018;Lauring and Selmer, 2018). However, the ethnicity and the country of origin of the SIE has not been openly discussed or empirically considered thus far.…”
Section: Discussionmentioning
confidence: 99%
“…In the present era, however, concerns for the many women who self-expatriate may also include ethnicity and how this is perceived in the host country. The way SIEs are treated, or perceive they are treated, in the host country workplace and the host-country in general, should have serious implications for their adjustment, performance and input for host country employers and the host country overall (Husssain and Deery, 2018). Being aware of how self-expatriate women, who compose a very substantial in size group, experience self-expatriation as function of their gender and ethnic origin is, therefore, of importance for host country employers, managers and officials.…”
Section: Discussionmentioning
confidence: 99%
“…Job embeddedness has been defined as "the combined forces that keep a person from leaving his or her job" [30]. After examining 204 self-initiated expatriates by Hussain and Deery [31], it was found that both on-the-job embeddedness and shocks can predict turnover intentions in the United Arab Emirates. Recently, the strong relevance of job embeddedness and turnover intentions was clearly highlighted by Afsar et al's [32] work, which suggested that job embeddedness fully mediates the relationship between high-performance work practices and turnover intentions.…”
Section: Job Embeddedness Job Satisfaction Affective Commitment Andmentioning
confidence: 99%